Study of Sustainable Gastronomy Tourism in Siantar City - Maleachi, Sandra; Juliana, Juliana; Sianipar, Rosianna; Sitorus, Nova Bernedeta (Jurnal Ilmiah Global Education, 2024)
This research aims to identify the sustainability of gastronomic tourism in Siantar City. The "Study of Sustainable Gastronomy Tourism in Siantar City" research uses a qualitative method. A gastronomic study of Siantar's culinary specialities, including roast pork, arsik carp, Siantar noodles, Siantar coffee, and traditional snacks, shows the richness of the city's culinary culture. The following conclusions can be drawn from this gastronomic study: (1) Cultural Heritage: The typical culinary delights of Siantar City are an inseparable part of the Batak cultural heritage. Each dish has a solid historical and traditional value, representing the identity of the people of Siantar City. (2) Uniqueness of Taste and Texture: Each dish has a unique taste and texture. Roast pork presents a combination of tender meat with crispy skin; arsik carp offers a unique blend of spicy, sour and distinctive flavours; bakmi Siantar has chewy noodles and savoury gravy; Siantar coffee has a distinctive aroma and rich taste, while jajanan pasar offers a wide variety of flavours. (3) Local and Tourist Influences: The typical culinary delights of Siantar City are favoured by residents and attract tourists. These foods are the main attraction for those who want to experience the delicacy and uniqueness of local cuisine. (4) Economic Impact and Tourism: Siantar City's unique cuisine has a significant economic impact. Culinary businesses, restaurants and coffee shops that serve these dishes provide employment and economic contribution to society. In addition, culinary specialities are also an attraction for tourists, which contributes to the development of the tourism sector in Siantar City. (5) Cultural Preservation: It is essential to pay attention to the preservation of Siantar City's unique culinary culture. Preservation efforts through documentation, training, promotion and quality improvement can maintain the sustainability and authenticity of these dishes so that future generations can enjoy them. This conclusion shows the importance of typical cuisine in enriching the cultural richness of Siantar City. These dishes not only meet the culinary needs of the local people but also have significant economic and tourism potential. Through preserving and developing unique culinary delights, Siantar City can continue to promote its distinctive and traditional culinary delicacies to the world.